PENGARUH SENYAWA BORON TERHADAP BEBERAPA SIFAT PAPAN PARTIKEL KARET (Hevea brasiliensis) - Rodjak Memed; I M Sulastiningsih; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
The objective of the study was to determine the effect of boron concentration and resin proportion on some properties of rubberwood (Hevea brasiliensis) particleboard. Boron concentrations used were 0, 0.25, 0.50, 0. 75 and 1.0%, and resin proportions in urea formaldehyde were 10, 12 and 14% dry weight basis.The results indicated that the addition of boron compound to porticleboard reduced the values of bending strength, internal bond strength and shear strength but increased the thickness swelling and water absorption of particleboard. Mechanical properties of particleboard increased with the increase of resin proportion. Thickness swelling and water absorption decreased as the resin proportion increases. Physical and mechanical properties of particleboard treated with boron compound up to 1% cocentration level and bonded with urea formaldehyde at 12% or 14% resin propotions were all met the SII standard requirements, except for internal bond strength. Compared with FAO standard, particleboards that met all the standard requirements were those with 14% resin proportion.